The League of Unexceptional Children - Daneshvari, Gitty (Little, Brown and Company, 2015)
Evanston, Virginia, twelve-year-olds Jonathan Murray and Shelley Brown are completely average and forgettable until they are recruited to help the League of Unexceptional Children save the Vice President of the United States, who has been kidnapped along with an important code